Vrozené vady u narozených detí v jednotlivých krajích Ceské republiky v období let 1994 - 2007 - Sípek, A; Gregor, V; Sípek, A; Horácek, J; Vencálek, O; Langhammer, P; Petrzílková, L; Wiesnerová, J (Ceska gynekologie, 2010)
AIM OF STUDY: An analysis of occurrence of birth defects in the Czech Republic regions in 1994 - 2007. An assessment of total numbers and relative incidences of birth defects in births according to Tenth Revision of International Classification of Diseases (ICD-10). TYP OF STUDY: Retrospective epidemiological analysis of birth defects incidences in the Czech Republic and its particular regions from the Czech National Birth Defects Register database. MATERIAL AND METHODS: Data from the National Birth Defects Register (Institute for Health Information and Statistics) in the Czech Republic in the 1994 - 2007 period were used. In this study, particular diagnoses--as they were registered in the National Register--were analyzed. The diagoses in study were divided into following eleven birth defects groups according to ICD-10 classification: (Q00-Q07) nervous system, (Q10-Q18) eye, ear, face and neck, (Q20-Q28) circulatory system, (Q30-Q34) respiratory system, (Q35-Q37) cleft lip and cleft palate, (Q38-Q45) digestive system, (Q50-Q56) genital organs, (Q60-Q64) urinary system, (Q65-Q79) musculoskeletal system, (Q80-Q89) other defects and (Q90-Q99) chromosomal abnormalities, not elsewhere classified. Prenataly diagnosed cases were not included. Birth defects in births were analyzed both in terms of the whole Czech Republic and its 14 particular administrative regions: Prague (the Capital City), Stredoceský, Jihoceský, Plzenský, Karlovarský, Ustecký, Liberecký, Královéhradecký, Pardubický, Vysocina, Jihomoravský, Olomoucký, Zlínský and Moravskoslezský. RESULTS: During 1994 - 2007 period, totally 1,353,040 children were born on the area of the Czech Republic, out of which 44,343 with a birth defect (totally 65,186 birth defects diagnoses). The diagoses in study were divided into eleven groups according to ICD-10 classification. Further, particular diagnoses according to ICD-10 and their verbal descriptions are presented in tables. Each group is accompanied by data on its total number and a relative incidence (per 10,000 live births) with a 95% C.I. A relative frequency of the birth defects groups in study (in % from the total number of birth defects) is as follows: (Q00-Q07) nervous system 2.10, (Q10-Q18) eye, ear, face and neck 4.76, (Q20-Q28) circulatory system 39.63, (Q30-Q34) respiratory system 1.03, (Q35-Q37) cleft lip and cleft palate 3.67, (Q38-Q45) digestive system 4.05, (Q50-Q56) genital organs 10.93, (Q60-Q64) urinary system 7.08, (Q65-Q79) musculoskeletal system 18.90, (Q80-Q89) other defects 5.55 and (Q90-Q99) chromosomal abnormalities 2.28. Relative number of birth defects per region (in % from the total number of birth defects) and deviations from a mean incidence of birth defects in the Czech Republic (total Czech Republic expressed as 100%, in brackets) were calculated for each particular region: Prague (the Capital City) 10.75 (97.82), Stredoceský 11.27 (102.25), Jihoceský 6.13 (99.53), Plzenský 5.27 (105.03), Karlovarský 3.09 (134.15), Ustecký 8.67 (118.03), Liberecký 4.38 (82.93), Královéhradecký 5.41 (112.14), Pardubický 5.04 (110.32), Vysocina 5.11 (99.43), Jihomoravský 10.76 (79.11), Olomoucký 6.16 (79.47), Zlínský 5.58 (90.60) and Moravskoslezský 12.39 (105.91). CONCLUSIONS: The study gives updated results of incidences analysis of birth defects in births in the Czech Republic and its 14 administrative regions during the 1994 - 2007 period. Variance in birh defects occurrence was found, reflecting more a distribution of incidences according to smaller administrative units (districts) than to a regional distribution. Less important differences in birth defects groups incidences between particular regions were also found.
Keywords: vrozené vady; Česká republika; Incidence; lidé; Female; Infant, Newborn; Pregnancy; incidence; těhotenství; novorozenec; Congenital Abnormalities; Czech Republic; ženské pohlaví; Humans